Comparative Analysis of Cash Buying and Murābaḥah Financing in Housing Transactions: Evidence from Green Mutiara Housing Banyumas Regency - Shinta Wahyuni (Journal of Economicate Studies, 2026)
The results of research conducted that in the process of purchasing cash housing Mutiara Hijau Tambaksogra At PT. Graha Perwira Pratama there are two that is credit and cash, home purchase in cash applied by PT. Graha Perwira Pratama branch of Housing Mutiara Hijau Tambaksogra Kembaran Sub-district of Banyumas Regency, there are two ways, namely: hard cash and gradually, while crediting in the application of payment with credit in green pearl housing Tambaksogra involves the bank through mortgage loan program and Financing Murabaha in Sharia Bank. In the murabaha method, the bank pays the home repayment to the developer. Comparison Purchase home in cash cheaper price, easier process, no administrative fees, free from the rules and more secure, while home purchase on credit does not need to save large amounts to buy a house, enough money to pay the down payment only and the greater the down payment or the longer the repayment period, the installment will become cheaper.